Land reform and its effect on farm household income inequality: Evidence from Georgia - Ayyāl Qimḥî (Economies, 2023)
This article examines the importance of landholdings in explaining income inequality among family farms in four districts in Georgia following the land reform of the 1990s. Income inequality is decomposed by sources of income and by determinants of income. The results indicate that farm income is a disequalizing source of income among family farms in these districts. In addition, a uniform increase in landholding is expected to reduce income inequality. Combining the two results, we conclude that the impact of land reform on farm household income inequality depends on the resulting distribution of landholdings. It can reduce inequality if land is distributed relatively equally, but inequality can increase if the wealthier farmers are able to gain control of more (and perhaps better) land resources. A possible implication of this result is that for land reform to be equalizing, distributing land to smallholders should be accompanied by additional policies and regulations supporting small farmers, such as land titling and registration, support for cooperation, and access to credit and other market services.
Keywords: 330; land reform; inequality decomposition; transition countries